HUBUNGAN MANAJEMEN LABA PADA SAAT INITIAL PUBLIC OFFERNG (IPO) DIENGAN KINERJA SAHAM PERUSAHAAN SETELAH IPO - Wahyuni, Endang Dwi (Journal of Innovation in Business and Economics, 2015)
This study was conducted to describe the earnings management practices of the company that did an IPO (Initial Public Offering) in Indonesia, and correlate earning management practices that did an IPO and stock performance after IPO. This study uses secondary data of financial statements that did an IPO, and stock price after IPO. Based on the criteria specified there are 54 companies that meet the criteria. Methods of data analysis using descriptive statistical analysis and correlation test to find the relationship earnings management practices prior to IPO stock per-formance after IPO. Results showed that 54 firms that did an IPO in 2010-2013, all of them have management practices. 72% decrease in profits and 28% of companies with profit increase. Based on the correlation test, the practice of earnings management before IPO negatively correlated to stocks performance after IPO.Keywords: Earning Management, IPO (Initial Public Offering), Stocks Performance